(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2017)
This research has tried to make a trip around the national experience in the continuous search to develop a very vulnerable sector of the population, not only from an environmental point of view, but socio-economic, rural areas of the country, and within it, small and medium farmers. For this, a series of documents and theoretical results both national and international have been consulted. The issue is not over; it’s just a slight idea of what developed nationwide. The results of each of the experiments have been implemented weakly reflected, and some shared. This opens a big challenge, start evaluating actual results over time each has had. Shared through these pages, lines might be a start.